Relationships among structural empowerment, psychological empowerment, intent to stay and burnout in nursing field in mainland China—based on a cross‐sectional questionnaire research. Issue 3 (17th December 2014) - Meng, Lina; Liu, Yanhui; Liu, Hongwei; Hu, Yu; Yang, Jipeng; Liu, Jingying
<x xml:space="preserve">Abstract</x> The aim of the study was to explore the relationship among perceived structural empowerment, psychological empowerment, burnout and intent to stay by nurses in mainland China.With the shortage of nurses in many countries, including China, intent to stay is a dominant factor to influence the quality of care. Also, burnout is identified to negatively affect the quality of care. Empowered clinical nurse practical environment is related to intent to stay and burnout. In the current literature, there is a lack of data based on empowering environment discussing the relationship between burnout and intent to stay. The study used an anonymous questionnaire, filled voluntarily by 219 nurses from different sections in a city in mainland China, 2012.Structural equation modelling (SEM) was used to test the proposed hypotheses. Based on the SEM model, structural empowerment and psychological empowerment had significant positive effects on intent to stay of nurses and negative effects on burnout. Burnout had a significant negative effect on intent to stay. The final modified models yielded χ2 = 58.580, P > 0.05, χ2/df = 1.046, root mean square error of approximation = 0.015, Tucker–Lewis Index = 0.996, comparative fit index = 0.998, which indicated good fit indices. Creating a positive empowering workplace can encourage nurses to stay long and prevent burnout. Therefore, higher level of empowering environment is required.